Identification and Functional Characterization of tRNA-derived RNA Fragments (tRFs) in Respiratory Syncytial Virus Infection - Wang, Qingrong (Nature Publishing Group, 2013)
The discovery of small noncoding RNAs (sncRNAs) with regulatory functions is a recent breakthrough in biology. Among sncRNAs, microRNA (miRNA), derived from host or virus, has emerged as elements with high importance in control of viral replication and host responses. However, the expression pattern and functional aspects of other types of sncRNAs, following viral infection, are unexplored. In order to define expression patterns of sncRNAs, as well as to discover novel regulatory sncRNAs in response to viral infection, we applied deep sequencing to cells infected with human respiratory syncytial virus (RSV), the most common cause of bronchiolitis and pneumonia in babies. RSV infection leads to abundant production of transfer RNA (tRNA)-derived RNA Fragments (tRFs) that are ~30 nucleotides (nts) long and correspond to the 5′-half of mature tRNAs. At least one tRF, which is derived from tRNA-Glu-CTC, represses target mRNA in the cytoplasm and promotes RSV replication. This demonstrates that this tRF is not a random by-product of tRNA degradation but a functional molecule. The biogenesis of this tRF is also specific, as it is mediated by the endonuclease angiogenin (ANG), not by other nucleases. In summary, our study presents novel information on the induction of a functional tRF by viral infection.